A water-stable luminescent metal–organic framework for effective detection of aflatoxin B1 in walnut and almond beverages. Issue 2 (2nd January 2019) - Li, Zhishang; Xu, Xiahong; Fu, Yingchun; Guo, Yuna; Zhang, Qi; Zhang, Qiaoyan; Yang, Hua; Li, Yanbin
Abstract : Sensitive and rapid detection of aflatoxin B1 (AFB1) without using antibody or biomolecular modifications in water is achieved using a novel water-stable luminescent metal–organic framework (LMOF) termed Zr-CAU-24. Abstract : Sensitive and rapid detection of aflatoxin B1 (AFB1) without using antibody or biomolecular modifications in water is achieved using a novel water-stable luminescent metal–organic framework (LMOF) termed Zr-CAU-24. The 1, 2, 4, 5-tetrakis(4-carboxyphenyl) benzene (H4 TCPB)-based LMOF with high water-stability has demonstrated drastic fluorescence fading in the presence of AFB1. The detection limit for AFB1 using this porous nanomaterial reaches as low as 19.97 ppb (64 nM), which is below the applicable action level for peanut and corn products set by the FDA and among the most sensitive sensors reported for AFB1. We further investigated its response to five other mycotoxins including AFB2, AFG1, AFG2, AFM and OTA and their Stern–Volmer quenching efficiencies are significantly below that of AFB1 (138 461 M −1 ). The prepared water-stable LMOF was directly used for the detection of AFB1 in spiked walnut and almond beverages. High recovery rates (91–108%) were achieved in 5 min. We found that the quenching of H4 TCPB molecules towards mycotoxins was remarkably enhanced by anchoring them into the periodic framework and its mechanism was discussed. The presented method with acceptable detection limit is of potential for the development of low-cost, robust and sensitive sensors for the rapid detection of AFB1 in agricultural and food products.